2022
DOI: 10.3389/fcvm.2022.792622
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Normal Reference Ranges for Non-invasive Myocardial Work Parameters in Pediatric Age: Results From an International Multi-Center Study

Abstract: AimsThis international multi-center study aimed to demonstrate the feasibility and reliability of non-invasive myocardial work (MW) parameters in the pediatric population, and to provide normal reference ranges for this useful echocardiographic tool in this specific subset of patients.Methods and ResultsIn this retrospective multi-center study involving three pediatric laboratories, 150 healthy children and adolescents (mean age of 10.6 ± 4.5, 91 males) were enrolled. A complete echocardiographic examination h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 22 publications
4
17
1
Order By: Relevance
“…In the meantime, our results confirmed but also extended previously published findings. We elucidated no influence of age, sex, BMI, HR, mitral annulus e , LVMI, LV sizes or LVEF on GMW indices in young people, in accordance with the previous reports across the different age groups (10,12,13,22). Interestingly, our study showed that SBP increased with age, whereas LV GLS decreases slightly with age in young people, which was in line with previous studies (22,24).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the meantime, our results confirmed but also extended previously published findings. We elucidated no influence of age, sex, BMI, HR, mitral annulus e , LVMI, LV sizes or LVEF on GMW indices in young people, in accordance with the previous reports across the different age groups (10,12,13,22). Interestingly, our study showed that SBP increased with age, whereas LV GLS decreases slightly with age in young people, which was in line with previous studies (22,24).…”
Section: Discussionsupporting
confidence: 93%
“…We elucidated no influence of age, sex, BMI, HR, mitral annulus e , LVMI, LV sizes or LVEF on GMW indices in young people, in accordance with the previous reports across the different age groups (10,12,13,22). Interestingly, our study showed that SBP increased with age, whereas LV GLS decreases slightly with age in young people, which was in line with previous studies (22,24). As the input variables for determining GMW indices, this inverse trend between SBP and LV GLS might explain the independence of GMW parameters from age.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations